Analysis of Digital Leadership and Police Personnel Performance in The Era of Technological Transformation - In Amur Rifqi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The rapid advancement of information and communication technology has compelled the Indonesian National Police (Polri) to undergo transformation through the implementation of digital leadership in order to enhance personnel performance and the effectiveness of public services. This study aims to examine the implementation of digital leadership within Polri, identify the challenges encountered during its execution, and analyze its impact on performance, service effectiveness, and personnel responsiveness in the era of digitalization. A mixed methods approach was employed, combining quantitative data collected through questionnaires with qualitative data obtained from interviews and focus group discussions (FGDs). The findings indicate that Polri has adopted digital leadership through the use of performance management applications and digital complaint systems, which contribute to the development of an adaptive and collaborative work culture. However, several challenges remain, including resistance to change, the dominance of hierarchical mindsets, limited access to digital training, and suboptimal system integration across work units. These issues have led to decreased motivation and reduced work effectiveness among personnel. Nevertheless, digital leadership has been shown to significantly improve performance, accelerate data-driven decision-making, and strengthen transparency and accountability in public service delivery. This study recommends enhancing digital competency training and improving technological integration as strategic steps to support the sustainable digital transformation of Polri.